2011
DOI: 10.1371/journal.pone.0020916
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA Expression in Psoriatic Skin: Reciprocal Regulation of hsa-miR-99a and IGF-1R

Abstract: BackgroundPsoriasis is a complex disease at the cellular, genomic and genetic levels. The role of microRNAs in skin development was shown in a keratinocyte-specific Dicer knockout mouse model. Considering that two main characteristics of psoriasis are keratinocytes hyperproliferation and abnormal skin differentiation, we hypothesized that aberrant microRNA expression contributes to the psoriatic phenotype. Here, we describe the differential expression of miRNAs in psoriatic involved and uninvolved skin as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
137
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 43 publications
8
137
0
2
Order By: Relevance
“…In recent years, with the comprehensive genetic analysis on miR, increasing numbers of specific miR have been discovered to be related with the pathology of psoriasis 19, including miR‐21 20, miR‐146a 21, miR‐424 22 and miR‐99a 23. Other previous studies have also shown that miR‐203, miR‐125b, miR‐99a and miR‐197 were relevant to the pathogenesis of psoriasis by regulating target genes 24, 25, 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the comprehensive genetic analysis on miR, increasing numbers of specific miR have been discovered to be related with the pathology of psoriasis 19, including miR‐21 20, miR‐146a 21, miR‐424 22 and miR‐99a 23. Other previous studies have also shown that miR‐203, miR‐125b, miR‐99a and miR‐197 were relevant to the pathogenesis of psoriasis by regulating target genes 24, 25, 26, 27.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover hsa-miR-125b was observed to regulate cell proliferation and differentiation in both breast cancer and ovarian cancer cell lines and plays an important role in osteoblastic differentiation (Iorio et al, 2005;Mizuno et al, 2008;Guan et al, 2011). Hsa-miR-125a-3p and hsa-miR-125a-5p were found to affect the migration and invasion of lung cancer cells, while hsa-miR-99a was found to affect the differentiation of keratinocytes (Jiang et al, 2010;Lerman et al, 2011). Recent evidence has shown that hsa-miR-155 may promote cell proliferation by regulating its target genes and can regulate the expression of the angiotensin II type 1 receptor in primary human lung fibroblasts (Kong et al, 2010;Martin et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…CTMs have been described in mice lacking genes involved in embryonic development [e.g., sonic hedgehog (6), Wnt (83,84), bone morphogenetic protein (85,86), FGFs (87,88)]. Recently, mice with cartilage-specific deletion of Dicer 1 showed abnormal tracheal development because of a lack of ECM deposition (89). Most of these mutant mice die embryonically or shortly after birth because of the severe and complicated embryonic defects.…”
Section: Discussionmentioning
confidence: 99%